2012
DOI: 10.1371/journal.pone.0030364
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characterization of Two Genes Encoding Dihydroflavonol-4-Reductase from Populus trichocarpa

Abstract: Dihydroflavonol 4-reductase (DFR, EC 1.1.1.219) is a rate-limited enzyme in the biosynthesis of anthocyanins and condensed tannins (proanthocyanidins) that catalyzes the reduction of dihydroflavonols to leucoanthocyanins. In this study, two full-length transcripts encoding for PtrDFR1 and PtrDFR2 were isolated from Populus trichocarpa. Sequence alignment of the two PtrDFRs with other known DFRs reveals the homology of these genes. The expression profile of PtrDFRs was investigated in various tissues of P. tric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 50 publications
1
44
0
Order By: Relevance
“…Duplication events involving DFR have been reported in several species, e.g., Zea mays and Teosinte guerrero 20, Ipomoea nil and I. purpurea 21, Medicago truncatula 22, Lotus japonicus 23, Populus trichocarpa 24, etc. In Scutellaria , gene duplication has been also evidenced by distinguishable intron lengths (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Duplication events involving DFR have been reported in several species, e.g., Zea mays and Teosinte guerrero 20, Ipomoea nil and I. purpurea 21, Medicago truncatula 22, Lotus japonicus 23, Populus trichocarpa 24, etc. In Scutellaria , gene duplication has been also evidenced by distinguishable intron lengths (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Most ABP genes, including DFR , are single-copy genes in several angiosperm species (e.g., Arabidopsis , Oryza , Vitis ). However, certain studies revealed DFR gene duplication in other species2021222324 and multiple copies of ABP genes were often found to be linked to whole genome duplication or tandem duplication (e.g., Brassica rapa 25, Lotus japonicus 26, Ipomoea sp 27…”
mentioning
confidence: 99%
“…Variable DFR –like gene numbers were therefore found in various genomes, e.g., a single copy DFR is present in Arabidopsis thaliana , in which the anthocyanin and proanthocyanidin components seemed to be simple as well, while multicopy DFR genes exist in M. truncatula, L. japonicus, Populus trichocarpa , and F. hybrida , these metabolites showed more complicated patterns and more diverse physiological functions (Østergaard et al, 2001; Xie et al, 2004; Shimada et al, 2005; Huang et al, 2012). Susumu Ohno hypothesized that gene duplication drives the evolution of novel functions, and deduced three kind fates of the duplicated genes: silence, neofunctionalization and subfunctionalization (Epstein, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in DFR may explain the color transition in some species such as Andean genus Iochroma (Des Marais and Rausher, 2008; Smith and Rausher, 2011; Smith et al, 2013). To our knowledge, various DFR genes have so far been isolated from a wide range of plant species, such as Lotus japonicus (Shimada et al, 2005), Camellia sinensis (Singh et al, 2009), Medicago truncatula (Xie et al, 2004), Malus domestica (Fischer et al, 2003), Pyrus communis (Fischer et al, 2003), Citrus sinensis (Piero et al, 2006), Ipomoea batatas Lam (Wang et al, 2013), Ginkgo biloba (Cheng et al, 2013), and Populus trichocarpa (Huang et al, 2012). However, most of the genes were isolated from dicot plants and few studies have focused on the functionally divergence of the members in the DFR gene family, especially in monocot species.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the ectopic expression of apple MdANR gene has been reported for higher proanthocyanidins and lower anthocyanins in tobacco flower (Han et al 2012). But the ectopic expression of PtrDFR1 has been reported to increase anthocyanins content, while ectopic expression of PtrDFR2 did not make any significant change in anthocyanins content of tobacco flower (Huang et al 2012). These two DFR proteins of same orthology were reported for different responses on flavonoids.…”
Section: Wwwplantrootorg 74mentioning
confidence: 99%